2022
DOI: 10.3389/fpsyg.2022.923094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traditional Behavior of Customers, Employees, and Social Enterprises on the Fear of Change and Resistance to Innovation

Abstract: Innovation adoption is the necessary element for the success of any organization around the globe, and this phenomenon needs a foremost solution. The current study examines this area and explores the impact of customers, employees, and social enterprises' traditional behavior on the resistance to innovation in social enterprises in China. The current article also investigates the mediating role of fear for change among customers, employees, and social enterprises' traditional behavior and resistance to innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…On the important reasons for consumers' change aversion can be their fear of cha "Change" is often linked with the idea of leaving something familiar behind and stepp into the unknown. Liu et al [47] indicated the vital role of fear of change in the custom traditional behaviors and among the people who are resisting innovation. The next fa affecting change aversion is the necessity of leaving their comfort zone, which can be ceived as both frightening and generating some risk of potential failure or disappointm [48].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the important reasons for consumers' change aversion can be their fear of cha "Change" is often linked with the idea of leaving something familiar behind and stepp into the unknown. Liu et al [47] indicated the vital role of fear of change in the custom traditional behaviors and among the people who are resisting innovation. The next fa affecting change aversion is the necessity of leaving their comfort zone, which can be ceived as both frightening and generating some risk of potential failure or disappointm [48].…”
Section: Theoretical Backgroundmentioning
confidence: 99%